Nivolumab plus ipilimumab versus the EXTREME regimen in recurrent/metastatic squamous cell carcinoma of the head and neck: a cost-effectiveness analysis - Dongmei Ye; Xueyan Liang; Xiaoyu Chen; Yan Li (Scientific Reports, 2024)
Abstract In the CheckMate 651 study, nivolumab plus ipilimumab versus EXTREME (cisplatin/carboplatin + cetuximab + fluorouracil) regimen was compared for effectiveness. It is not known whether these immunotherapy agents are cost-effective for recurrent or metastatic squamous cell carcinomas of the head and neck (R/M SCCHN). The purpose of this study was to compare the cost-effectiveness of nivolumab plus ipilimumab with EXTREME in the first-line setting from the standpoint of third-party payers in the United States. The projecting of costs and outcomes over 15 years was done using a three-state partitioned survival model discounted by 3% per year. Long-term extrapolation of CheckMate 651 was used to model progression-free survival and overall survival (OS). The incremental net health benefit (INHB), incremental net monetary benefit (INMB), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) were calculated. The uncertainty and stability of the model were accounted for via one-way and probabilistic sensitivity analyses. As compared with nivolumab plus ipilimumab, EXTREME was associated with an increase of 0.154 life-years and 0.076 QALYs, as well as a cost increase of $572 per patient. The corresponding ICERs were $7545/QALY along with the values of INMB and INHB were $113,267 and 0.076 QALYs, respectively, at a willingness to pay (WTP) threshold of $150,000/QALY. The probability of nivolumab plus ipilimumab being cost-effective was > 99% in patients with combined positive score (CPS) ≥ 1, CPS 1–19, or CPS ≥ 20. Moreover, hazard ratio for OS and body weight were the most sensitive parameters for the model. According to sensitivity analyses, these results were generally robust. In overall populations with R/M SCCHN, the EXTREME regimen is cost-effective compared with nivolumab plus ipilimumab. Given a WTP threshold of $150,000 per QALY, the probability of the EXTREME regiment being cost-effective compared with nivolumab and ipilimumab, was 64%. Importantly, there was heterogeneity in the cost-effectiveness probabilities, based on primary sites and expression levels of PD-L1. Therefore, tailored treatment based on individual patient and clinical characteristics, remains important, and may impact the cost-effectiveness of the regimens under study.